Auditory Brainstem Implants: Recent Progress and Future Perspectives - Wong, Kevin; Kozin, Elliott D.; Kanumuri, Vivek V.; Vachicouras, Nicolas; Miller, Jonathan; Lacour, Stéphanie; Brown, M. Christian; Lee, Daniel J. (Frontiers in Neuroscience, 2019)
The auditory brainstem implant (ABI) was first developed nearly 40 years ago and provides auditory rehabilitation to patients who are deaf and ineligible for cochlear implant surgery due to abnormalities of the cochlea and cochlear nerve. The aims of the following review are to describe the history of the ABI and innovations leading up to the modern ABI system, as well as highlight areas of future development in implant design.